Effects of different protease treatment on protein degradation and flavor components of Lentinus edodes. Issue 6 (1st November 2022) - Fang, Xiangjun; Chen, Ziqi; Wu, Weijie; Chen, Hangjun; Nie, Shaoping; Gao, Haiyan
Abstract: Shiitake mushrooms ( Lentinus edodes ) form a great source of protein; however, the effect of enzymatic hydrolysis to improve its flavor has not yet been investigated. To explore the effects of different protease treatments on protein degradation and flavor compounds of shiitake mushrooms, papain, neutral protease, and flavourzyme were selected for the hydrolysis of shiitake mushrooms. Proteolysis index, Trichloroacetic acid‐nitrogen soluble index, and protein content were estimated to evaluate protein degradation. Flavor amino acids and volatile components of the hydrolysate were also analyzed. Results showed flavourzyme has an advantage over the others in promoting protein degradation and improving flavor. Compared to single‐enzyme treatment, a combination treatment with three enzymes, at 1:1:1 ratio, was found to perform greater protein hydrolysis. After protease‐mediated hydrolysis, the variety and content of flavor substances (free amino acids and eight‐carbon compounds) in L. edodes increased. We concluded that protease treatment is an effective method for improving the quality and flavor of L. edodes . Abstract : Flavourzyme promoted protein degradation and improved flavor of Lentinus edodes. Combining the 3 enzymes at a 1:1:1 ratio had the best protein hydrolyzing effect. Protease treatment increased flavor substance variety and content in L. edodes.